The Relationship Between Nutritional Status and Cognitive Function in The Elderly In The UPT Area of The City Health Center Surakarta - Indry Wulansari; Brian Wasita; Muthmainah (Future Science, 2024)
With age comes changes in the nervous system that are associated with a decline in cognitive function. Impaired cognitive function in the elderly is in the form of decreased memory, language, decision-making, and action. Nutritional status can be related to cognitive function. Measurement of nutritional status can be done by calculating body mass index (BMI) to determine the risk of malnutrition or obesity. Based on data from the Indonesian Psychogeriatric Organization (2019), states that the elderly aged 50-59 years experience a decrease in cognitive function in the form of forgetfulness with a mild category (Mild Cognitive Impairment) with a prevalence of 39%. To determine the relationship between nutritional status and cognitive function in the elderly in the UPT Puskesmas Surakarta City area. The design in this study was observational analytic with a Cross-Sectional approach. Samples in the study were taken by Simple Random Sampling of as many as 110 elderly people at the Surakarta City Health Center. Nutritional status in this study was measured by Body Mass Index (BMI) and cognitive function was carried out by interviewing the Mini-Mental State Examination (MMSE) questionnaire. Data analysis used the Chi Square test (?=0.05). In this study, there were elderly with a nutritional status less with a percentage of 50%, normal 6.4%, and more nutritional status 43.7% while elderly with moderate cognitive function decline with a percentage of 34.5%, mild cognitive function decline 49.1% and no decline in cognitive function with a percentage of 16.4%. The results of this study indicate that there is a significant relationship between nutritional status and cognitive function in the elderly in the UPT Puskesmas Surakarta City area with (p=0.001). There is a significant relationship between nutritional status and cognitive function in the elderly in the UPT Puskesmas Surakarta City area. Based on research (Dewi, 2019), states that the elderly with poor nutritional status is caused by changes in intestinal function, metabolic changes and deficiencies in nutrient intake while the elderly with more nutritional status experience changes in body composition with central fat accumulation in the abdomen so that it is related to decreased cognitive function.